Influence Of Elicitors On Saponin And Proline Production In Suspension Cultures Of Gymnema Sylvestre R Br. (Applied Biological Research, 2016)
Diabetes mellitus is a major disorder of key concern worldwide. So, the plants having anti-diabetic  property are of significant interest. Gymnema sylvestre R.Br., a member of family Asclepiadaceae,  is a potent anti-diabetic plant. It is a large, woody, much branched, slow growing perennial climber  having pubescent young parts. This mesophytic to xerophytic plant is found in tropical to sub
Keywords: Influence; Cultures Of Gymnema; Sylvestre